(untitled) (Gestão & Regionalidade, 2017)
The municipal governments’ capital structure is constantly influenced by intergovernmental transfers that characterize the Brazilian fiscal federalism. These transfers are part of the fiscal decentralization process and their main objective is to reduce the socioeconomic inequalities in a country featured by large territorial extensions, as in Brazil. That being said, this study aimed to analyze the implications of municipal fiscal effort (measured from the representation of own tax collection in the revenue available to local governments) on the socioeconomic development of the municipalities. The field of analysis of this study comprises the municipalities of Minas Gerais, Brazil, because it is the state with the largest number of municipalities and that presents significant regional disparities resulting from the coexistence of modern and backward regions. The results showed that there is a strong relationship between effort and development, since municipalities where there is more tax collection, also showed a higher level of socioeconomic development.